The Influence of the External Environment on Business Strategy Planning and Implementation - Ari Purwanti; Loso Judijanto; Najdah Thalib (Westscience Press, 2023)
This research investigates the influence of the external environment on business strategy planning and implementation in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through a quantitative analysis. The study encompasses a diverse sample of participants representing various industries, business sizes, and geographic locations. Perceived impacts of external factors, such as economic conditions, technological changes, regulatory factors, and competitive forces, were assessed. Additionally, the study explored the success of business strategy formulation and implementation across different industries. A regression analysis was conducted to uncover relationships between external factors and business strategy success. The findings reveal industry-specific nuances, emphasizing the importance of tailored strategies for MSMEs in Indonesia. The research contributes to the understanding of strategic management in the MSME sector and provides insights for policymakers and practitioners seeking to enhance the resilience and growth of these enterprises.